Peningkatan Motivasi Belajar IPA Melalui Strategi Time Token Siswa Kelas IV SDN Majegan 3 Tahun Ajaran 2015/2016 - Maulina, Betty, Dra. Risminawati, M.Pd (2016)
This study aims to (1) increase the motivation to learn science grade IV SDN Majegan 3 2015/2016 academic year through strategies Time Token (2) improve learning outcomes IPA grade IV SDN Majegan 3 2015/2016 academic year through the strategy Time Token. This research is the Classroom Action Research (PTK). The subjects in this study were teachers and students of class IV SDN Majegan 3 totaling 15 students. While the object is motivation to learn science by implementing strategies Time Token. The technique of collecting data through interviews, observation, and documentation. The data analysis technique consists of data reduction, data presentation, and conclusion. The results showed an increase in student motivation of prasiklus, the first cycle, the second cycle which includes five aspects of indicators of motivation to learn, which include: The existence of desire and managed 36.66%, 54.16% and 79.16%, have a sense of trust self 40%, 57.49% and 81.66%, vigorously 43.33%, 59.99% and 83%, have a high curiosity 36.66%, 55.83% and 77.5%, able to walk alone when the teacher asks the students to do something 35%, 50.83% and 75.83%. Time Token learning strategies also improve student learning outcomes in prasiklus 26.66%, 66.66% the first cycle and the second cycle 86.66%. The conclusion of this study is through a strategy Time Token can enhance motivation and learning outcomes IPA grade IV SDN Majegan 3 of the school year 2015/2016.